Effect of the exogenous testosterone on the penis-prepucial adherences and fiber production in Huacaya alpacas - Oscanoa, Alex (2017)
The effect of testosterone on penis-prepucial adherences and production of fibre was studied in 30 alpacas. Animals were 18 months old and were distributed in three groups: without treatment (T0), treated with testosterone enanthate (0.5 mg/kg/body weight) every two weeks during 12 weeks (T2E), and castrated (C0). The penis-prepucial adherences, testicular size, sexual behavior and body weight were evaluated every two weeks, and fibre samples were collected at the beginning of the study and at the end of three experimental periods. In a 4-week pre-experimental phase all parameters were evaluated for adjusting the data of the experimental phase. Release of penis-prepucial adherences was greater in T2E than in T0 and C0 between weeks 8 (p<0.001) and week 12 (0.006>p<0.001). Higher testicular size (length, width, and thickness) occurred in T0 than in T2E between weeks 4 and 12 (0.01>p<0.0001). Fibre diameter was similar in T2E and T0, but were greater than in C0 (p<0.05). Clean and greasy fibre weights were similar in all groups. The clean fibre yield was less in T2E than T0 and C0 in the periods II and III (0.04>p<0.0001). Body weight was greater in T2E than in T0 and C0 (p<0.05). It was concluded that the administration of testosterone to young male alpacas was effective in releasing penis-prepucial adherences and in body weight increase, but decreased the testicular size and clean fibre yield; however, did not affect the clean and greasy fibreweights, and fibre diameter.